2015
DOI: 10.1007/s00264-015-2988-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome and T2 assessment following autologous matrix-induced chondrogenesis in osteochondral lesions of the talus

Abstract: The one-step autologous subchondral cancellous bone grafting and AMIC leads to a significant reduction in postoperative pain and satisfying postoperative functional outcome in mid-term follow-up. Magnetic resonance imaging (MRI) assessment demonstrated a good quality of regenerative tissue similar to the MRI ultrastructure of the surrounding cartilage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
63
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 26 publications
7
63
1
1
Order By: Relevance
“…However, the increase of MOCART score was not correlated with AOFAS score changes. Similarly to our results, Aurich et al did not find any correlation between MOCART and clinical scores after treatment with AMIC technique for OLTs [16] whereas, as we reported above, Kubosch et al found a significant correlation [14]. As suggested by Christensen and colleagues, a thorough radiological follow-up for patients with OLTs repaired using biomimetic scaffolds is recommended [8].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, the increase of MOCART score was not correlated with AOFAS score changes. Similarly to our results, Aurich et al did not find any correlation between MOCART and clinical scores after treatment with AMIC technique for OLTs [16] whereas, as we reported above, Kubosch et al found a significant correlation [14]. As suggested by Christensen and colleagues, a thorough radiological follow-up for patients with OLTs repaired using biomimetic scaffolds is recommended [8].…”
Section: Discussionsupporting
confidence: 87%
“…After a mean follow up of 39.5 ± 18.4 months, they also found a significant correlation between MOCART and AOFAS score [14]. In our study, MOCART score showed improvement of imaging findings after surgery.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The most important of which reported significant improvement in functional outcomes and MOCART scores, which demonstrated a good quality repair tissue similar to the MRI ultrastructure of the surrounding cartilage at an average of 2 year follow-up. 52 Although this seems to be promising, several studies in the knee have shown inferior reparative response on MRI with incomplete or heterogeneous fill. 53,54 This raises the question of whether there is a sufficient concentration of the MSC niche in the AMIC membrane to support chondrogenesis and repair of critical-sized defects, with questionable long-term durability that might affect results.…”
Section: Autologous Matrix-induced Chondrogenesismentioning
confidence: 97%
“…Despite AMIC showing good functional outcomes in the literature, most studies are small case series and, to our knowledge, no study has described the long-term outcomes. Kubosch et al [45] reported 17 patients following AMIC for medial OLT with a mean 39.5 months of follow-up and found that the mean postoperative AOFAS score was 82.6 and the Magnetic Resonance Observation of Cartilage Repair Tissue (MOCART) score was 52.7. MRI assessment demonstrated a good quality of regenerative tissue similar to the MRI ultrastructure of the surrounding cartilage.…”
Section: Autologous Matrix-induced Chondrogenesismentioning
confidence: 99%